The Impact Covid-19 to Financing SMEs Sharia Banking In Indonesia - Abdullah, Muhammad Ruslan; Fasiha, Fasiha (Universitas Islam Negeri Alauddin Makassar, 2021)
In the economy recovery, banking are required to keep exist provide financing to the perpetrators of the business, especially sharia bank which is identical with the real sector. SMEs in a normal situation are very difficult to get funding due to the non-fulfillment of the requirements that must be met to obtain funding , what is about the corona virus pandemic condition? How is the condition of Islamic banking in providing financing for SMEs?Â The results of the study found that the sharia banks financing is not experiencing an increase or stagnate. On the other , Equivalent levels of rewards in Sharia General Bank and in percent experienced a decrease but not significantly, and so also with the level of average margin financing on SMEs percent experienced a decrease but not significantly. The results of the analysis are obtained conclusion that the bank sharia in Indonesia affected pandemic Covid-19.